DETEKSI ANEMIA REMAJA PUTRI MELALUI PEMERIKSAAN KADAR HAEMOGLOBIN - Reineldis Elsidianastika Trisnawati; Imelda R. Dewi; Fransiska N. Nanur; Maria Lourdes (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Until now anemia in adolescent girls is still the main problem of adolescent health in Indonesia. The problem of anemia in adolescent girls every year continues to increase around 1 in 5 adolescents. In 2013, as many as 32% of adolescents had anemia. Given the magnitude of the impact of anaemia on adolescent girls, various interventions have been made by the government that focus on providing iron tablets, micronutrients, increasing food diversity and food security. This service activity was carried out at Vocational High School Karya Ruteng. The purpose of this service activity is to increase the knowledge of adolescent girls about anemia and increase the awareness of adolescents to consume iron tablets, especially during menstruation, and to detect early adolescent girls with anemia status through haemoglobin examination. The results of this activity have a positive impact on adolescents, during counseling activities adolescents are very enthusiastic about listening to the material explained and the results of the adolescent posttest about anemia are mostly good knowledge 83% while the results of the Hb level examination are known from 30 adolescents who are examined 33.3% with anemia. The results of this activity are expected to be an input for adolescent women about the importance of consuming blood-boosting tablets, especially during the menstrual period